The effect of commercial rice husk ash additives on the porosity, mechanical properties, and microstructure of alumina ceramics - Ali, Mohammed Sabah; Hanim, M. A. Azmah; Tahir, S. M.; Jaafar, C. N. A.; Mazlan, Norkhairunnisa; Matori, Khamirul Amin (Hindawi Publishing Corporation, 2017)
A porous ceramic is made from composite materials which consist of alumina and commercial rice husk ash. This type of ceramics is obtained by mixing the commercial rice husk ash as a source of silica (SiO2) and a pore forming agent with alumina (Al2O3) powder. To obtain this type of ceramic, a solid-state technique is used with sintering at high temperature. This study also investigated the effects of the rice husk ash ratios on the mechanical properties, porosity, and microstructure. The results showed that, by increasing the content of the rice husk ash from 10 to 50 wt%, there is an increase in the porosity from 42.92% to 49.04%, while the mechanical properties decreased initially followed by an increase at 30 wt% and 50 wt%; the hardness at 20 wt% of the ash content was recorded at 101.90 HV1. When the ash content was increased to 30 wt% and 50 wt%, the hardness was raised to 150.92 HV1 and 158.93 HV1, respectively. The findings also revealed that the tensile and compressive strengths experienced a decrease at 10 wt% of the ash content and after that increase at 30 wt% and 50 wt% of rice husk ash. XRD analysis found multiple phases of ceramic formation after sintering for the different rice husk ash content.